- Include technology topics and standards of learning content of science curricula for students in the primary stage in Saudi Qassim - descriptive study - Al Saad, Fahad Mohammed Saeed (Journal of Educational and Psychological Sciences, 2018)
The current study aimed to identify the extent to which technology subjects and their learning standards include the content of science curricula for primary school students. The study applied the analytical descriptive method. A tool was used to analyze the content of the science books for primary school students in the fourth and fifth grades in the light of the technology learning criteria required for the students of that stage in the Asir region of education in Saudi Arabia. The tool included three main themes: materials, technological tools, technological design, and technology fields. The study found that there was a deficiency. This percentage reached 11.78% (28.6%) in the treatment of science textbooks in the primary stage of the subjects and standards of learning the technology necessary for that important stage. Developing students’ technological skills, which helps them design, and technological production of simple models to solve some life problems. The study recommended a number of recommendations that emphasized the importance of including in the science curricula for students in the primary stage topics and standards of learning technology and related positions, and educational experiences to keep pace with the innovations of scientific education and teaching science for the twenty-first century.